Kualitas Air Bersih Masyarakat Di Sekitar Tempat Pembuangan akhir (TPA) Sampah Talumelito - Hasan, Ruslin; Suleman, Rahman; Ali, Indra Haryanto (Jurnal Kesehatan Lingkungan, 2022)
Final Disposal Site (TPA) The existence of a waste Final Processing Site (TPA) has the potential to be a source of water pollution. This study is a descriptive study, the sample used in this study is water used by the community around the Talumelito TPA location, which was taken at 5 different points. The results showed that of the 5 water samples taken, the pH, temperature, and TDS parameters met the requirements, while for turbidity, there were 2 samples taken from point 2 and point 3 that did not meet the requirements because they had a turbidity value of 26.7 NTU, and 26.9 NTU. This result is not in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 32 of 2017, namely the NAV for water turbidity is 25 NTU. The conclusion of this study is that the turbidity for the samples obtained from point 2 and point 3, which is clean water consumed daily by the people in that place, does not meet the requirements. Meanwhile, the parameters of pH, temperature, and TDS in water taken from 5 sampling locations met the requirements.